2022
DOI: 10.2478/prolas-2022-0043
|View full text |Cite
|
Sign up to set email alerts
|

Shedding of Coxiella Burnetii in Milk of Dairy Cattle and Evidence of Q Fever in Domestic Ruminants with Emphasis on Abortion Cases in Latvia

Abstract: Q-fever is widespread globally. The goal of this study was to estimate the prevalence of Q-fever infection in Latvia among dairy cattle in 2018–2020, in comparison with that in 2012–2015. The shedding of Coxiella burnetii DNA in milk was assessed. Screening of blood samples of abortion cases for the presence of antibodies against Q-fever and testing of aborted fetuses for C. burnetii DNA were also carried out. Additionally, serum samples from clinically healthy cattle, sheep and goat were included. Overall, 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Many studies that looked at individual cows found that seropositivity was associated with the prevalence of the ASPW complex. For example, a recent study [53] reported that the seropositivity rate of aborted cows was higher than that of non-aborting cows. Also, based on the presence of C. burnetii DNA in BTM and/or aborted foetuses, they noted that 18.3% of herds were positive.…”
Section: Abortion Stillbirth Perinatal Mortality and Weak Offspring (...mentioning
confidence: 99%
“…Many studies that looked at individual cows found that seropositivity was associated with the prevalence of the ASPW complex. For example, a recent study [53] reported that the seropositivity rate of aborted cows was higher than that of non-aborting cows. Also, based on the presence of C. burnetii DNA in BTM and/or aborted foetuses, they noted that 18.3% of herds were positive.…”
Section: Abortion Stillbirth Perinatal Mortality and Weak Offspring (...mentioning
confidence: 99%